2019
DOI: 10.1038/s41418-018-0259-4
|View full text |Cite
|
Sign up to set email alerts
|

MORC2 regulates C/EBPα-mediated cell differentiation via sumoylation

Abstract: The expression and activity of CCAAT/enhancer-binding protein α (C/EBPα) are involved in sumoylation modification, which is critical to divert normal cells from differentiation to proliferation. However, the role and underlying mechanism of C/EBPα in cancer is poorly understood. Human MORC2 (microrchidia family CW-type zinc-finger 2), is a member of the MORC proteins family containing a CW-type zinc-finger domain. Here, we found that MORC2 interacted with TE-III domain of C/EBPα, and the overexpression of MORC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Mutations in genes involved in neuronal/muscular differentiation, and differentiation defects were linked to dHMNs. For example, IGHMBP2 leads to differentiation defects in motoneurons and is mutated in Charcot–Marie–Tooth (CMT) 2S; 73 MORC2 is a chromatin-remodeling protein regulating differentiation and mutated in CMT; 74 NDRG1 promotes differentiation and is mutated in CMT4D; 75 Sbf1/Sbf2 are epigenetic regulators of cell differentiation and are mutated in CMT 76 , 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes involved in neuronal/muscular differentiation, and differentiation defects were linked to dHMNs. For example, IGHMBP2 leads to differentiation defects in motoneurons and is mutated in Charcot–Marie–Tooth (CMT) 2S; 73 MORC2 is a chromatin-remodeling protein regulating differentiation and mutated in CMT; 74 NDRG1 promotes differentiation and is mutated in CMT4D; 75 Sbf1/Sbf2 are epigenetic regulators of cell differentiation and are mutated in CMT 76 , 77 .…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] C/EBPα posttranslational modifications including ubiquitination, which is catalyzed by E3 ubiquitin ligases have been shown to regulate both function and expression of C/EBPα. 5,[11][12][13][14][15][16] In a previous study, we also reported reduced C/EBPα steady-state levels through enhanced ubiquitin-mediated proteasome degradation by E6AP. 17 However, mechanisms regulating C/EBPα protein stability in diseases are poorly known.…”
Section: Introductionmentioning
confidence: 61%
“…Therefore, dysregulated expression and functional inhibition of C/EBPα is associated with block in myeloid differentiation and leukemogenesis . C/EBPα posttranslational modifications including ubiquitination, which is catalyzed by E3 ubiquitin ligases have been shown to regulate both function and expression of C/EBPα . In a previous study, we also reported reduced C/EBPα steady‐state levels through enhanced ubiquitin‐mediated proteasome degradation by E6AP .…”
Section: Introductionmentioning
confidence: 70%
“…Several studies have shown that expression of the core SUMOylation machinery (E1 activating enzyme, E2 conjugating enzyme, several E3 ligases, and SUMO1/sentrin specific peptidases) is enhanced in GC, 7–10 suggesting that SUMOylation is closely related to the survival and malignant behavior of GC cells. However, only a few transcription factors and receptors such as forkhead box protein C2 (FOXC2), N‐myc downstream‐regulated gene 2 (NDRG2), Sp1, CCAAT/enhancer‐binding protein alpha (C/EBPα), insulin‐like growth factor 1 receptor (IGF‐1R), and death domain‐associated protein 6 (DAXX) have been reported to be SUMOylated in GC 10–15 . Uncovering the roles of more SUMOylated proteins in GC will provide a promising perspective for investigating the molecular mechanism of tumorigenesis and progression, finding novel biomarkers with higher sensitivity, and contributing to the early diagnosis and targeted therapies of GC.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few transcription factors and receptors such as forkhead box protein C2 (FOXC2), N-myc downstreamregulated gene 2 (NDRG2), Sp1, CCAAT/enhancer-binding protein alpha (C/EBPα), insulin-like growth factor 1 receptor (IGF-1R), and death domain-associated protein 6 (DAXX) have been reported to be SUMOylated in GC. [10][11][12][13][14][15] Uncovering the roles of more SUMOylated proteins in GC will provide a promising perspective for investigating the molecular mechanism of tumorigenesis and progression, finding novel biomarkers with higher sensitivity, and contributing to the early diagnosis and targeted therapies of GC. Tuftelin (TUFT1) was initially characterized as a protein involved in tooth enamel mineralization in vertebrates and subsequently found in nonmineralized tissues such as lung, stomach, and liver.…”
mentioning
confidence: 99%